Reconstruction of ventro-lateral hernia in female buffalo calf using sterilized double layer mosquito net - Kumar, Pradeep; Kuldeep, Shantanu Kumar; Kumar, Raj (Buffalo Bulletin, 2020)
A six months old female buffalo calf was brought to clinic, having history of accident with automobile followed by small swelling at the right ventro-lateral abdominal region that increased gradually to size of football thereafter. Clinical and ultrasonographic examinations revealed hernation of small intestine. Surgical correction was recommended due to large dimension of hernial ring and economic value of the animal. Hernial ring was repaired by using sterilized mosquito net. Superficial muscles and skin was closed in routine manner. Animal was followed up for 3 months post operatively and positive results were observed. This procedure was found to be cost effective and not associated with major complication.